2012
DOI: 10.1097/nmd.0b013e31825322cf
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Suicidal Ideation and Related Risk Factors in the German General Population

Abstract: The present study aimed to determine the prevalence of suicidal ideation in a representative sample of the German general population and examined its relation to potential risk factors. The study sample consisted of 2509 persons. Mean age was 49.4 years (SD, 18.2 years; 55.8% women). Participants filled in the Hospital Anxiety and Depression Scale and two items from the Rasch-based Depression Screening measuring suicidal ideation. Suicidal ideation was reported by 8.0% (n = 211) of all participants. People rep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
32
2
12

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 68 publications
(50 citation statements)
references
References 24 publications
4
32
2
12
Order By: Relevance
“…Suicidal ideation was measured with a single item. Despite this being common practice in this area of research [1,2,59] the use of psychometric scales for suicidal ideation would be desirable and may improve the reliability of assessments in future investigations. Strengths include the large sample size and sufficient power for the analysis of group by time interaction effects.…”
Section: Strengths and Limitationsmentioning
confidence: 98%
See 2 more Smart Citations
“…Suicidal ideation was measured with a single item. Despite this being common practice in this area of research [1,2,59] the use of psychometric scales for suicidal ideation would be desirable and may improve the reliability of assessments in future investigations. Strengths include the large sample size and sufficient power for the analysis of group by time interaction effects.…”
Section: Strengths and Limitationsmentioning
confidence: 98%
“…Several population-based studies revealed point prevalences of suicidal ideation in the general population ranging from 5% up to 10% [1][2][3][4]. In clinical samples, the prevalence of suicidal ideation is much higher.…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…Important risk factors for suicide in older adults include physical illness, financial problems, marital status, gender, chronic pain, race, loss of social ties, and social isolation (Juurlink et al, 2004; Sirey et al, 2008; Forkmann et al, 2012; Morrell et al, 1998; Barraclough, 1971). There is some evidence from cross sectional studies that certain cognitive deficits in older individuals increase their risk for suicidal behavior.…”
Section: Introductionmentioning
confidence: 99%
“…자살생각과 관련된 요인을 좀 더 살펴 보면, 건강수준, 질병여부, 비만, 수면 등이 자살 생각과 관련된다고 보고된 바 있으며 [10], 결혼상태, 학력, 흡연 등도 자살생각과 관련이 있고 [8], 동 반가족 없이 혼자 사는 경우 자살생각률이 높은 것으로 보고되었다 [12]. 자살생각을 가진 사람들 중 여성, 젊은 나이, 낮은 학력과 수입, 미혼, 경제 활동이 없거나 정신장애가 동반된 사람들이 자살 행동이나 자살 시도가 더 많았다 [13].…”
unclassified